PERAN E-PERPUS NGUDI ILMU SEBAGAI UPAYA PELESTARIAN BUDAYA BACA MASYARAKAT - Irbilil Wahdaniatish Shohih; Salsabilla Windari; Mega Alif Marintan (2025)
This research aims to provide a deeper understanding of how digital libraries can be a strategic tool in building a community reading culture in the increasingly advanced digital era. The research method used is to use a descriptive qualitative method with data collection, namely by interview, observation and documentation. The results of the study show that the Ngudi Ilmu E-Perpus application combines the functions of education, information and community empowerment in one platform that can be accessed online. The role of E-Perpus Ngudi Ilmu is as an effort to preserve the reading culture of the community, E-Perpus Ngudi Ilmu is used as an additional reference by educators and E-Perpus Ngudi Ilmu is used as a means of recreation with its collection. With this application, people can read books more easily and flexibly, both children and adults and support teaching and learning activities. Although there are still obstacles such as the low ability of the community to use technology (digital literacy) and the limited number of book collections, this library continues to strive to provide socialization and update the contents of its collection so that reading interest is maintained. The presence of the Ngudi Ilmu E-Perpus proves that the village library can also keep up with the times and remains an important place to improve reading culture in the community